Effective way of treatment in local sanitation with 25% dimexidе solution in patients with purulent surgical diseases - B.B.Safoev; Т.Sh.Boltaev; К.Z.Rakhimov (Proceedings of The ICECRS, 2019)
Despite the development of modern technology and new methods of treating purulent wounds, it remains relevant. The number of patients with acute purulent diseases of the soft tissues is up to 35-40% of all surgical patients and has a tendency to increase.